A hPSC-based platform to discover gene-environment interactions that impact human β-cell and dopamine neuron survival. Issue 1 (December 2018) - Zhou, Ting; Kim, Tae; Chong, Chi; Tan, Lei; Amin, Sadaf; Sadat Badieyan, Zohreh; Mukherjee, Suranjit; Ghazizadeh, Zaniar; Zeng, Hui; Guo, Min; Crespo, Miguel; Zhang, Tuo; et al.
Abstract Common disorders, including diabetes and Parkinson's disease, are caused by a combination of environmental factors and genetic susceptibility. However, defining the mechanisms underlying gene-environment interactions has been challenging due to the lack of a suitable experimental platform. Using pancreatic β-like cells derived from human pluripotent stem cells (hPSCs), we discovered that a commonly used pesticide, propargite, induces pancreatic β-cell death, a pathological hallmark of diabetes. Screening a panel of diverse hPSC-derived cell types we extended this observation to a similar susceptibility in midbrain dopamine neurons, a cell type affected in Parkinson's disease. We assessed gene-environment interactions using isogenic hPSC lines for genetic variants associated with diabetes and Parkinson's disease. We foundGSTT1 −/− pancreatic β-like cells and dopamine neurons were both hypersensitive to propargite-induced cell death. Our study identifies an environmental chemical that contributes to human β-cell and dopamine neuron loss and validates a novel hPSC-based platform for determining gene-environment interactions. Diseases such as diabetes and Parkinson's manifest based on interactions between genes and environment. Here, the authors find among a panel of cell types that propargite, a common pesticide, induces pancreatic β-cell and dopamine neuron death and that loss of the gene GSTT1 confers hypersensitivity.